A vueltas con el amor y el gozo en la Tragicomedia de Calisto y Melibea - Matos, Kevin (El Colegio de México, 2021)
Without discarding altogether readings taht emphasize the moralizing aspects of the work, in this article I intend to explore the plausibility of privileging pleasure, rather than morality, as the principal purpose of the Tragicomedia. To do so, I turn to the ambiguous texts of naturalist erotology, according to which love is a natural and ineluctable force that always cancels out reason, being itself a source of great delight. A careful reading of these related texts obliges us to relativize any reading of Celestina.